PENGEMBANGAN SISTEM INFORMASI KINERJA DOSEN BERBASIS WEB DALAM UPAYA MENINGKATKAN KOMPETENSI DOSEN DI UNIV. INDO GLOBAL MANDIRI - Terttiaavini Terttiaavini; Rita Wirya Saputra (UNIVERSITAS INDO GLOBAL MANDIRI)
The Evaluation of Lecturer Performance is a regularly procedure that runs by a High Education Institution as assesment process and follow up all of the Policy from The Quality Control Unit. The Key Performance Indicator of the lecturer at Indo Global University so far only base on lecture aspec. Meanwhile, base on to the Policy, it should be refer to the Tridharma Peguruan Tinggi activities as well. Base on to this matter born out an Idea to desgning a Lecturer Performance Evaluation Information System at UIGM with the Tridharma Peguruan Tinggi activities and Lecutrer Competancy as a key indicator web basis. The application designed as problem solving tool such as collecting data and reporting. By utility of the System Development Waterfall Method and the 360 Degree Assement Method, hopeful could be improving the Lecturer Performance Evaluation Information System. The research has resulting a describe of achievement of the lecturer competancy on previous semester. It also could be come an best input for management of the university to preparing and decided a policy, planning and strategy in order to increasing the quality and competancy of the lecturer at UIGM.Key word : Sistem informasi evaluasi Kinerja Dosen, Model Waterfall, Metode 360 Degree, Aplikasi web.